2021
DOI: 10.9734/jpri/2021/v33i55a33799
|View full text |Cite
|
Sign up to set email alerts
|

Assess the Prevalence for Needs of Breast Cancer Survivors' in the Oncology Ward at a Selected Tertiary Care Hospital

Abstract: The unmet needs of breast cancer survivors are not being addressed as the number of survivors continues to climb. Aim and Objective: To determine the prevalence of post-treatment unmet needs and association between unmet needs of breast cancer survivors with selected demographic variables. A descriptive research study was conducted in a tertiary care hospital's oncology outpatient clinic and wards. Materials and Methods: Data was gathered in two sections: I – baseline data, and section II – Modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(36 citation statements)
references
References 5 publications
2
34
0
Order By: Relevance
“…Fear of disclosure [12,14,22,27,28,35,38,45], feelings about death and dying [7,37,46,47], and uncertainty about the future [7,37,43,47] were the next highest-ranked needs. Other psychological and emotional needs included stigma associated with cancer [4,14], frustration [30], low mood and isolated needs [30], and feelings of sadness [47]. In the study by Autade et al (2021), all breast cancer survivors reported emotional needs, including worry, anxiety, depression, anger, frustration, low mood, and isolated needs [30].…”
Section: Evidence Of Unmet Supportive Care Needs By Domainmentioning
confidence: 97%
See 4 more Smart Citations
“…Fear of disclosure [12,14,22,27,28,35,38,45], feelings about death and dying [7,37,46,47], and uncertainty about the future [7,37,43,47] were the next highest-ranked needs. Other psychological and emotional needs included stigma associated with cancer [4,14], frustration [30], low mood and isolated needs [30], and feelings of sadness [47]. In the study by Autade et al (2021), all breast cancer survivors reported emotional needs, including worry, anxiety, depression, anger, frustration, low mood, and isolated needs [30].…”
Section: Evidence Of Unmet Supportive Care Needs By Domainmentioning
confidence: 97%
“…Psychological/emotional needs: 32 studies described the psychological and emotional needs of breast cancer survivors [4,7,13,14,22,23,. The most frequently reported psychological and emotional needs were depression, anxiety, and stress (N=15) [4,23,27,30,34,38,[43][44][45][46][47][49][50][51] and fears about cancer spread and recurrence (N=13) [7,23,28,34,37,39,43,44,46,47,[49][50][51]. In the study conducted by Bu et al (2022), fear of recurrence was identi ed as the most important need in breast cancer survivors; it was reported by 69% of patients [44].…”
Section: Evidence Of Unmet Supportive Care Needs By Domainmentioning
confidence: 99%
See 3 more Smart Citations